Kajian Peran Mikroorganisme Tanah Dalam Pertanian Berkelanjutan - Harefa, Listari; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Soil serves as the medium for plant growth, where plants absorb nutrients to support their development. Soil fertility is influenced by the availability of nutrients that plants can absorb. These nutrients are essential for physiological processes and plant structure formation. This article discusses the role of soil microorganisms in sustainable agriculture, where the diversity and health of microorganisms contribute to biogeochemical cycles and the balance of the soil ecosystem. Microorganisms such as bacteria, actinomycetes, fungi, algae, and protozoa play a significant role in supplying nutrients for plants.